Performance analysis of palm, jatropha and moringa biodiesels in a diesel engine / Md. Mofijur Rahman - Md. Mofijur , Rahman (2013)
The global energy consumption is expected to grow in a faster rate than the population growth. By 2030, an increase of 53% of global energy consumption and 39% of greenhouse gases emissions from fossil fuels are anticipated. Therefore, it has become a global agenda to develop clean alternative fuels which are domestically available, environmentally acceptable and technically feasible. As an alternative fuel, biodiesel seems as one of the best choices among other sources due to its environment friendly aspect and similar functional properties as diesel fuel. This research aims to produce biodiesel from some edible and non-edible oils that are either readily available or have native distribution in Malaysia. These oils include; Palm (Elaeis guineensis), Jatropha curcas and Moringa oleifera oils. This was followed by a detailed investigation of physic-chemical properties of the produced methyl esters such as kinematic viscosity, density, flash point, cloud point, pour point, cold filter plugging point, viscosity index and oxidation stability. This research also discusses the concept of biodiesel-diesel blending to improve some of the properties. Moreover, 5%, 10%, 15% and 20% by volume blends of Palm, Jatropha curcas and Moringa oleifera were used to evaluate their performance in a Mitsubishi Pajero turbocharged diesel engine. According to the results of the investigation, the produced methyl esters meet biodiesel standard specification. Moreover, blending of biodiesel with diesel fuel improves their fuel properties. The results of engine performance indicated that over the entire range of speed, biodiesel blended fuels give average reduction in torque, brake power and increased brake specific fuel consumption values compared to diesel fuel. In case of engine emission, biodiesel blended fuels give an average reduction in carbon monoxide and hydrocarbon emissions whereas slightly increased nitric oxides and carbon dioxides emissions respectively compared to diesel fuel. Overall, Palm biodiesel blended fuel showed better performance than Jatropha curcas and Moringa oleifera biodiesel blended fuels. In conclusion, Palm, Jatropha curcas and Moringa oleifera are potential feedstock for biodiesel production, and up to 20% of their blends should be considered to replace diesel fuel without engine modification to reduce the dependency on petro-diesel and produce cleaner exhaust emissions.